Exophthalmos as a first manifestation of the systemic spread of small cell lung cancer - Obuchowska, Iwona; Mariak, Zofia; Pawluczuk, Barbara (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Small cell lung cancer is characterized by rapid growth and early metastases. The most frequent locations of the secondary lesions include adrenal glands, brain, liver, and skeleton. On initial diagnosis, up to 70% of patients with small cell lung cancer have metastases. Metastases to the eye or orbit developen approximately 0.7–12% of patients with lung cancer. Clinical signs and symptoms of orbital metastases may include exophthalmos, diplopia, pain, limited ocular motility, blurred vision, swollen eyelid, conjunctival hyperemia and edema, increased ocular pressure and papilledema. Here, we report a rare case of exophthalmos as the first manifestation of a metastatic tumor of orbit due to small cell lung cancer.